Developing the Potential of Health Promotion Hospital Management of Roi Et Provincial Administration Organization: Developing the Potential of Health Promotion Hospital Management of Roi Et Provincial Administration Organization - Wainiampong, Sekasit; sangranoo, surapong (RATANABUTH JOURNAL, 2026)
This study aimed to: (1) examine the managerial capacity in overseeing the transferred functions of Subdistrict Health Promoting Hospitals (SHPHs) under the Roi Et Provincial Administrative Organization; (2) investigate the factors influencing managerial capacity; and (3) propose guidelines for enhancing the managerial capacity of SHPHs under the Roi Et Provincial Administrative Organization. The study employed a qualitative research methodology. A total of 30 key informants were selected through purposive sampling, comprising three groups: policy and executive-level personnel, operational and managerial staff, and network partners and stakeholders. Data were collected through semi-structured in-depth interviews. Data credibility was ensured through data and source triangulation, as well as member checking. Data were analyzed using content analysis. The findings revealed that: (1) overall managerial capacity demonstrated notable development, particularly in policy structure and participatory management. Organizational structures were designed to be flexible, adapting to the size of service units, alongside decentralized management of operational funds. However, limitations remained due to inconsistencies between local regulations and professional public health standards, as well as shortages of operational-level personnel. (2) Five key dimensions influencing managerial capacity were identified: strategic leadership, organizational culture integration, network trust, fiscal stability, and digital readiness. Among these, leadership and trust-building were the most critical factors. (3) Proposed development guidelines include area-based cluster management, the establishment of career progression and welfare plans for personnel, provincial-level management of pharmaceuticals and medical supplies, integration of digital health databases, and strengthening governance networks to enhance the efficiency and sustainability of the primary healthcare system.